KURIKULUM INTRA DAN EKSTRA KURIKULER PADA MAN I SAMARINDA DAN RELEVANSINYA DENGAN PERKEMBANGAN MUATAN LOKAL - Rosdiana Rosdiana (Balai Penelitian dan Pengembangan Agama Makassar, 2009)
Research aims to describe and identify the local content elements incurriculum applied in MAN I Samarinda, and related community response.From the findings, it shows that Madrasah Aliyah Negeri 1Samarinda has implemented in its learning process the program ofskill development on dressmaking, welding, automotive, and computertechniques and integrated it with local content elements. Manyparties have had good responses saying that the school as religiousbased instruction institution has breasted the times as it has beencapable to combine the religious knowledge, skill and science. Theirpositive response comes as they believe that the skill developmentprogram could prepare the student to be able to go in labour marketcompetition.